Gas-phase endstation of electron, ion and coincidence spectroscopies for diluted samples at the FinEstBeAMS beamline of the MAXIV 1.5GeV storage ring - Kuno Kooser; Antti Kivimäki; Paavo Turunen; Rainer Pärna; Liis Reisberg; Marco Kirm; Mika Valden; Marko Huttula; Edwin Kukk (INT UNION CRYSTALLOGRAPHY, 2022)
Since spring 2019 an experimental setup consisting of an electron spectrometer and an ion time-of-flight mass spectrometer for diluted samples has been available for users at the FinEstBeAMS beamline of the MAXIV Laboratory in Lund, Sweden. The setup enables users to study the interaction of atoms, molecules, (molecular) microclusters and nanoparticles with short-wavelength (vacuum ultraviolet and X-ray) synchrotron radiation and to follow the electron and nuclear dynamics induced by this interaction. Test measurements of N-2 and thiophene (C4H4S) molecules have demonstrated that the setup can be used for many-particle coincidence spectroscopy. The measurements of the Ar3p photoelectron spectra by linear horizontal and vertical polarization show that angle-resolved experiments can also be performed. The possibility to compare the electron spectroscopic results of diluted samples with solid targets in the case of Co2O3 and Fe2O3 at the Co and Fe L-2,L-3-absorption edges in the same experimental session is also demonstrated. Because the photon energy range of the FinEstBeAMS beamline extends from 4.4eV up to 1000eV, electron, ion and coincidence spectroscopy studies can be executed in a very broad photon energy range.